Adverse events after catheter ablation of atrial fibrillation: a comprehensive nationwide cohort study - Lappalainen, Antti; Hartikainen, Juha E. K.; Teppo, Konsta; Halminen, Olli; Aro, Aapo L.; Karvonen, Jarkko; Siponen, Rasmus; Marjamaa, Annukka; Salmela, Birgitta; Putaala, Jukka; Mustonen, Pirjo; Linna, Miika; et al. (Springer Nature, 2026)
Background
Catheter ablation is frequently used for rhythm control of atrial fibrillation (AF). However, nationwide, real-world data on the incidence of adverse events and their predictors following the procedure remain limited.
Methods
Finnish AntiCoagulation in Atrial Fibrillation (FinACAF) is a registry-linkage study including all patients with AF in Finland between 2007 and 2018. We investigated the incidence and predictors of new-onset adverse events following all first-time AF catheter ablations (3075 patients) in Finland between 2012 and 2016.
Results
At the one-month follow-up, 1.14% and by two years 6.34% of the patients experienced an adverse event or died. At one-month follow-up, 0.33% of patients developed ischaemic stroke or transient ischaemic attack (IS/TIA). The incidence of IS/TIA was 6.6 times higher during the first 19 days after ablation compared to the subsequent follow-up period. The incidence of IS/TIA after anticoagulation discontinuation was low: 0.8 events per 100 patient-years. The most frequent events during two-year follow-up were bleeding (2.44%), IS/TIA (1.82%), and heart failure (1.24%). Older age was associated with all-cause mortality, bleeding, heart failure and combined endpoint of adverse events during two-year follow-up. Women presented with a higher risk of IS at the time of ablation, but the sex-related difference attenuated during the follow-up. Additionally, the CHA₂DS₂-VA score predicted IS, but not the combined endpoint of IS/TIA or TIA alone, during the follow-up period.
Conclusion
In this nationwide, real-world cohort, older age, especially ≥ 70 years, emerged as the strongest risk factor for adverse events after first-time catheter ablation for AF.